Análisis jurídico de la gestión organizacional, competencias y atribuciones del Registro de la Propiedad del cantón Guaranda. - Hinojoza Espín María José (2025)
This research work, titled "Legal Analysis of Organizational Management, Competences, and Attributions of the Property Registry of Guaranda Canton," seeks to conduct a legal analysis of the organizational management of the Property Registry. It thoroughly examines the attributions, roles, and competences within the institution, which holds significant responsibility for registering important data for citizens, data that is closely linked to legal procedures related to their assets. This study aims to clarify the responsibilities of the Property Registry in accordance with current legal regulations and to analyze how organizational management influences the effectiveness of fulfilling these responsibilities. Furthermore, it is necessary to gain a deeper understanding of the functioning and legal regulation of the Property Registry in Guaranda Canton to identify potential issues and critical points. It is noteworthy that this institution has existed practically since the Ecuadorian State became a Republic. The regulations governing it have not changed over time and are among the oldest in Ecuadorian legislation, despite the need for the law to be updated and adapted to social changes and needs. The Property Registry Law has not undergone changes since it was enacted in 1966 through Supreme Decree No. 1405. However, in fulfilling its function, the Assembly promulgated the Organic Law of the National System of Registration and Public Data in 2010 to protect personal data, ensure legal security, organize, regulate, systematize, and interconnect information, and improve the efficiency and effectiveness of its management, publicity, transparency, access, and the implementation of new technologies. All this is closely related to the Property Registry because this entity is part of this extensive state system and must logically contribute and adapt to legal organizational management to achieve positive results. With the above, this work aims to contribute to legal and administrative knowledge related to the Property Registry, focusing on strengthening legal security and confidence in the registration system of Guaranda Canton, thereby benefiting the community at large. As a descriptive investigation, it will use descriptive methods to define, categorize, classify, and characterize the object of study. The research methodology is both qualitative and quantitative, utilizing the dogmatic and interpretative method of constitutional and legal norms. These methods provide a response to the addressed issue based on the best possible reconstruction allowed by the available legal material. Moreover, since the social phenomena studied in this work are measurable and quantifiable, I will measure and establish causal relationships between variables to explain the study problem and the current social reality. Keywords: Property Registry, Organizational Management, Institutional Processes, Principle of Publicity, Legal Norm Update.